Caraway (Carum carvi L.) in fast-growing and slow-growing broiler chickens' diets and its effect on performance, digestive tract morphology and blood biochemical profile - Šťastník, Ondřej; Novotný, Jakub; Roztočilová, Andrea; Zálešáková, Dana; Řiháček, Michal; Horáková, Lucie; Pluháčková, Helena; Pavlata, Leoš; Mrkvicová, Eva (Poultry science, 2022)
The aim of this study was to evaluate the addition of caraway (1%) in fast-growing and slow-growing broiler chickens' diet and its effect on performance parameters, blood biochemical profile, and relative organ sizes and ileum morphology in slow-growing broilers. Two separated experiments were performed. On the first day of age, the broilers were divided into 2 equal groups (Control and Caraway) with 6 replicates per treatment in both experiments. Experiment I: The total of 276 male fast-growing Ross 308 broiler chickens were used. The trial lasted from the first day to 35th day of chickens' age. Experiment II: The total of 216 male slow-growing (Hubbard JA 57) broilers were used. The trial lasted from the first to 50th day of chickens' age. Mean liveweight, weight gain, feed conversion ratio, blood biochemical parameters, and relative organ sizes were not significantly different in these trials. The group of slow-growing broilers supplemented with 1% of caraway in the diet showed longer villi and deeper crypt in the ileum after 50 d of life. Based on our results, it can be stated that the proportion of 1% caraway in fast-growing and slow-growing broiler chickens' diet did not influence performance parameters, blood biochemical profile and relative organ sizes. In case of the experiment with the slow-growing broilers supplemented with caraway, a significant difference in the height of the villi and the depth of the crypts was found. Caraway can be included in the broiler chickens' diets without negative effects, but further study of the effect on the intestinal morphology is necessary.
Keywords: gastrointestinální trakt; dieta; Animal Nutritional Physiological Phenomena; krmivo pro zvířata; ileum histomorphometry; potravní doplňky; limonene; carvone; Gastrointestinal Tract; mužské pohlaví; phytogenic feed; kur domácí; fyziologie výživy zvířat; Chickens; kmín; zvířata; Carum; Dietary Supplements; Animal Feed; villus; Diet; Male; Animals